(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
The main problem of ferry ships is maintaining the speed due to ship resistance. There are many efforts to reduce the resistance by modifications of them. This study aims to reduce resistance due to modification of the hull form on the bow Angle of Entrance (AoE) and ducktail addition at the transom stern. The object of the research is a 1,500 GT ro-ro ferry. The AoE minimizes wave resistance and improves flow patterns, while the ducktail reduces the negative effects of the circulation zone on the wetted transom so that waves and wake are reduced. Computational Fluid Dynamics (CFD) was used to analyze these modifications. The final results of the numerical simulation are then verified by the ship model resistance test in the towing tank. Tests were conducted in calm water conditions at a draft of 3.30 meters with a speed variation of 10 - 18 knots. The results show that with the combination of AoE and Ducktail, at ship speeds of 13 to 18 knots, the reduction in resistance from CFD ranges from 13.13% - 16.69% while the experimental results range from 16.00% - 16.54%. While separately the AoE modification is between 8.89% – 12.19% and ducktail is 3.12% -3,62%.